Jordan : Background Information on Selected Aspects of Adjustment and Growth Strategy. (IMF Staff Country Reports; Country Report ;, 1995)
This paper presents background information on selected aspects of adjustment and growth strategy for Jordan. The paper deals with the key developments in the Jordanian economy since 1989 compared with its developments in the 1970s and 1980s. It presents an overview of Jordan's economic structure, policies, and developments, particularly since 1989, and provides a setting for the issue-oriented discussions of other sections. Although highlighting Jordan's recent success, it stresses the importance of appropriate financial policies and structural reforms, together with external financial support, for achieving sustainable economic growth.